R versus D, from knowledge creation to value appropriation: ownership of patents filed by European biotechnology founders - Fabiano, G; Marcellusi, A; Favato, G (Elsevier, 2021)
Biotechnology firms are often created on the premise of commercialising the results of research carried out by scientists with heterogeneous careers and research trajectories. Patents filed by company founders provide accessible information on the appropriation of knowledge through the assignment of intellectual property rights (IPR).